Solid-state structures of 4-carboxyphenylboronic acid and its hydrates - SeethaLekshmi, Nanappan; Pedireddi, Venkateswara Rao (Crystal Growth & Design, 2007)
Solid-state structures of 4-carboxyphenylboronic acid (1a) and its mono- and quarter-hydrates (1b and 1c, respectively) obtained by crystallization from different solvents, acetone, methanol, and 2-proponal, respectively, have been reported. In the anhydrous and monohydrate structures (1a and 1b), the H-atoms on the -B(OH)(2) functional group exist in syn-syn conformation, but syn-anti conformation was found in the quarter-hydrate structure. While 1a and 1b crystallize through interactions between -B(OH)(2) and -COOH groups (heteromeric), homomeric interactions of the functional groups (COOH center dot center dot center dot COOH and B(OH)(2)center dot center dot center dot B(OH)(2)) were observed in 1c. In addition, although similar interactions prevail in 1a and 1b, the latter crystallizes in a noncentrosymmetric space group Ccc2, registering itself as a unique structure with unusual catenation features with the aid of water molecules. However, 1a and 1c show many common features in the molecular arrangement in the crystal lattices with the formation of sheet structures.